Atrophy and Primary Somatosensory Cortical Reorganization after Unilateral Thoracic Spinal Cord Injury: A Longitudinal Functional Magnetic Resonance Imaging Study. (29th December 2013) - Rao, Jia-Sheng; Manxiu, Ma; Zhao, Can; Xi, Yue; Yang, Zhao-Yang; Zuxiang, Liu; Li, Xiao-Guang
Abstract : The effects of traumatic spinal cord injury (SCI) on the changes in the central nervous system (CNS) over time may depend on the dynamic interaction between the structural integrity of the spinal cord and the capacity of the brain plasticity. Functional magnetic resonance imaging (fMRI) was used in a longitudinal study on five rhesus monkeys to observe cerebral activation during upper limb somatosensory tasks in healthy animals and after unilateral thoracic SCI. The changes in the spinal cord diameters were measured, and the correlations among time after the lesion, structural changes in the spinal cord, and primary somatosensory cortex (S1) reorganization were also determined. After SCI, activation of the upper limb in S1 shifted to the region which generally dominates the lower limb, and the rostral spinal cord transverse diameter adjacent to the lesion exhibited obvious atrophy, which reflects the SCI-induced changes in the CNS. A significant correlation was found among the time after the lesion, the spinal cord atrophy, and the degree of contralateral S1 reorganization. The results indicate the structural changes in the spinal cord and the dynamic reorganization of the cerebral activation following early SCI stage, which may help to further understand the neural plasticity in the CNS.